The Influence of Partner Contribution, Control, Conflict, Communication and Interdependence - Nowaz, Rushaid (2005)
Globalization is creating a fundamental shift in the world economy. In a world where the volume of goods, services and investment crossing national borders is expanding faster than world output every year, where the pendulum of public policy in nation after nation is swinging towards the free market end, where the opportunities for both small and big businesses to expand revenues, lower costs and increase profits are rising, globalization is essentially revolutionizing the mannerisms of conducting business, intensifying competition and shortening product life cycles (Hill, 2005). Managers are realizing that the strength and resources possessed by their firms are no longer able to maintain a cutting edge at every step of the value creating chain. Thus, strategic alliances are playing an influential role in aiding business organizations adapt to the diversifying world of business activities. However, in spite of the increase in international strategic alliance [ISA’s] activity in recent years, researchers state that the landscape is littered with failures. There is a lack of research that understands the ingredients for successful strategic alliances. The objective of this thesis therefore is to reveal to the readers the state of affairs of international strategic alliances in Malaysia by paying attention to how the five “literature indicated important variables,” namely: partner contribution, control, conflict, communication and interdependence influence the success of international strategic alliances.